NUTRITIONAL FACTORS AND THEIR ROLE IN MENTAL HEALTH - A CLINICAL REVIEW - Oliwia Wróblewska; Jakub Majewski; Barbara Pająk; Maria Kaniecka; Anna Karcz; Artur Koza; Hubert Bołdys-Żegocki; Małgorzata Dworniczak; Sofiya Salash; Aleksandra Romaniuk (International Journal of Innovative Technologies in Social Science, 2025)
The aim of this study was to review the current scientific evidence on the effects of selected nutrients on mental health in the general population. Randomized controlled trials, metaanalyses, and systematic reviews published between 2018 and 2025 were analyzed, retrieved from the PubMed, Embase, and Google Scholar databases. The review considered associations between the intake of omega-3 fatty acids, B-group vitamins, vitamin D, zinc, magnesium, probiotics, prebiotics, and antioxidants (vitamins C, E, carotenoids, and polyphenols) and the occurrence of depressive, anxiety, and cognitive symptoms. Literature data indicate that deficiencies of these nutrients may affect neurotransmitter function, neuronal plasticity, inflammatory processes, and oxidative stress, linking diet to the pathophysiological mechanisms of mood disorders. Supplementation with omega-3 fatty acids, folic acid, magnesium, zinc, vitamin D, and selected probiotics demonstrated moderate improvement in mood and reduction of anxiety symptoms in most analyzed studies, while the results for vitamins C, E, and B₁₂ remain inconclusive. Beneficial effects of curcumin and βcarotene were also observed in reducing oxidative stress and improving psychological wellbeing. The collected data suggest that an adequate supply of micronutrients and antiinflammatory components may support mental health, but the current evidence is limited by small sample sizes, short observation periods, and heterogeneity of interventions. In clinical practice, a balanced diet remains essential, while supplementation should be individualized and applied in cases of confirmed deficiency. This article summarizes the current state of knowledge and indicates directions for future research.